Development and Application of a Python Program Simulating the Orbit of a Lunar Probe - Fan, Zhenming; Huang, Zichen (Transactions on Computer Science and Intelligent Systems Research, 2024)
This paper presents the development and application of a Python program designed to simulate the orbital trajectory of a lunar probe using the fourth-order Runge-Kutta (RK4) method, a method known for its accuracy and computational efficiency. The program models the entire journey of a lunar probe, from its initial launch on the Earth to its stable circular orbit around the Moon. By allowing users to input specific parameters for acceleration and deceleration phases, the program generates orbital paths relative to both the Earth and the Moon, offering valuable insights into mission planning and trajectory optimization. One significant application demonstrated in this paper is the simulation of the Chang’e 5 mission, China’s first lunar sample return mission. By incorporating Doppler data from Chang’e 5, the program effectively simulates the probe’s orbital path, highlighting its potential for future real-world lunar exploration missions. Despite some simplifying assumptions, such as treating the Earth as a perfect sphere and assuming instantaneous acceleration, the program provides a robust framework for simulating lunar probe trajectories with high accuracy and computational efficiency.